2005
DOI: 10.1080/14622200500266056
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of moderate‐intensity exercise as an aid for smoking cessation in women: A randomized controlled trial

Abstract: Evidence suggests that vigorous-intensity exercise interventions may be effective for smoking cessation among women; however, few studies have examined the efficacy of a moderate-intensity exercise program. The present study examined the efficacy of moderate-intensity exercise for smoking cessation among female smokers. Healthy, sedentary female smokers (N = 217) were randomly assigned to an 8-week cognitive-behavioral smoking cessation program plus moderate-intensity exercise (CBT+EX) or to the same cessation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
265
2
24

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(298 citation statements)
references
References 40 publications
7
265
2
24
Order By: Relevance
“…Similar results were found for sedentary women smokers that were introduced into an aerobic training program combined with a cognitive-behavioral program 37 , where this evidence points to an increase in cessation rates and maintenance of tobacco abstinence among those that participate in the physical exercise program. Other articles in the literature 38,39 also corroborate our findings.…”
Section: Discussionsupporting
confidence: 70%
“…Similar results were found for sedentary women smokers that were introduced into an aerobic training program combined with a cognitive-behavioral program 37 , where this evidence points to an increase in cessation rates and maintenance of tobacco abstinence among those that participate in the physical exercise program. Other articles in the literature 38,39 also corroborate our findings.…”
Section: Discussionsupporting
confidence: 70%
“…A Cochrane review concluded, however, that while exercise promotion did not appear to harm smoking cessation efforts, there was limited evidence that it helped (Ussher, 2005). Only one of the 11 identified trials (Marcus, et al, 1999) found evidence for exercise aiding smoking cessation at long term follow-up. Unfortunately, only two of the studies reported changes in physical activity, limiting our understanding of the feasibility of smokers making changes in their tobacco use and exercise patterns concurrently.…”
Section: Or Diabetes (Diabetes Prevention Programmentioning
confidence: 99%
“…Unfortunately, only two of the studies reported changes in physical activity, limiting our understanding of the feasibility of smokers making changes in their tobacco use and exercise patterns concurrently. Of note, the one study that had significant effects for both quitting smoking and increasing fitness matched exercise and smoking cessation strategies to participants' readiness to quit, rather than prescribing immediate action (Marcus, et al, 1999).…”
Section: Or Diabetes (Diabetes Prevention Programmentioning
confidence: 99%
“…Our research with women has demonstrated that aerobic exercise coupled with CBT produces higher quit rates at posttreatment (30.6 vs. 21.8 %) and 6-month follow-up (24.6 vs. 13.6 %) than CBT without exercise [16]. Unfortunately, studies of exercise as a complementary treatment to smoking cessation have either focused exclusively on women, or have enrolled men and women, but have not reported gender-specific outcomes [17].…”
Section: Introductionmentioning
confidence: 89%